1985
DOI: 10.1002/j.1460-2075.1985.tb04120.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transfer of genetic information between gram-positive and gram-negative bacteria.

Abstract: A 1427‐bp DNA fragment containing the kanamycin resistance gene, aphA‐3, of plasmid pIP1433 from Campylobacter coli was inserted into a shuttle vector. Full expression of aphA‐3 was obtained in Bacillus subtilis and in Escherichia coli. This DNA fragment was sequenced in its entirety and the starting point for aphA‐3 transcription in B. subtilis, C. coli and E. coli was determined by S1 nuclease mapping. The sequence of the promoter consists of the hexanucleotides TTGACA and TATAAT, with a spacing of 17 bp. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
126
1
2

Year Published

1988
1988
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(134 citation statements)
references
References 37 publications
4
126
1
2
Order By: Relevance
“…Plasmid pILL836 (Fig. 2) resulted from the introduction of a 1.5 kb XmaI fragment carrying a kanamycin resistance gene (aphA-3), derived from pILL575 (Labigne et al, 1991) under the control of its own promoter (Trieu-Cuot et al, 1985) into the XmaI site of pILL835.…”
Section: Hybridization Experiments and Construction Of Plasmidsmentioning
confidence: 99%
“…Plasmid pILL836 (Fig. 2) resulted from the introduction of a 1.5 kb XmaI fragment carrying a kanamycin resistance gene (aphA-3), derived from pILL575 (Labigne et al, 1991) under the control of its own promoter (Trieu-Cuot et al, 1985) into the XmaI site of pILL835.…”
Section: Hybridization Experiments and Construction Of Plasmidsmentioning
confidence: 99%
“…PCR was carried out using H. pylori NCTC 11637 chromosomal DNA, and the resulting amplicon was cloned into HincIIdigested pGEM 3Zf (1) (Perkin-Elmer). The 1.1 kb kanamycin resistance gene, aphA-3, from C. coli (Trieu-Cuot et al, 1985) was then cloned into a unique StyI site within the HP0686 gene to generate pJV302. For inactivation of the tonB-like gene, a 787 bp fragment of HP1341 was PCR amplified from H. pylori 26695 chromosomal DNA and cloned into pCR2.1 according to the TA cloning protocol (Invitrogen) (forward primer 5 H -AATTTCTCCATCTCCACGCAAGCTCA-3 H ; reverse primer…”
mentioning
confidence: 99%
“…However, antibiotic resistance determinants from gram-positive bacteria are often expressed in gram-negative microorganisms, whereas the reverse is uncommon (7,20,40). From analysis of the nucleotide sequences and the deduced amino acid sequences of aminoglycoside and macrolide resistance genes, it has been concluded that a horizontal transfer of genetic material from gram-positive to gram-negative bacteria must have occurred (4,39,40,42).…”
mentioning
confidence: 99%